Pengaruh Brand Image dan Promosi terhadap Loyalitas Pelanggan pada Split Espresso Coffee Shop Kota Blitar - Silviana Dita Fernanda; Hanik Amaria; M. Halim Fawazi (Jurnal Manajemen Bisnis Era Digital, 2025)
The purpose of the study was to determine the effect of brand image and promotion on customer loyalty at Split Espresso Coffee Shop, Blitar City. The research method chosen was quantitative descriptive, with a research sample of 100 respondents. Sampling used a purposive sampling technique that met the criteria as Split Espresso Coffee Shop customers in Blitar City who had visited twice or more. The results of the study showed that the brand image variable had a significant value of 0.000 <0.05, which means that partially brand image had an effect on customer loyalty, the promotion variable had a significant value of 0.707> 0.05, and partially promotion had no effect on customer loyalty. The results of the simultaneous test of significant value 0.000 <0.05, which means that all variables simultaneously affect customer loyalty at Split Espresso Coffee Shop, Blitar City.